2021
DOI: 10.3390/polym13071137
|View full text |Cite
|
Sign up to set email alerts
|

Improving Rheological and Mechanical Properties of Various Virgin and Recycled Polypropylenes by Blending with Long-Chain Branched Polypropylene

Abstract: Blends of two long-chain branched polypropylenes (LCB-PP) and five linear polypropylenes (L-PP) were prepared in a single screw extruder at 240 °C. The two LCB-PPs were self-created via reactive extrusion at 180 °C by using dimyristyl peroxydicarbonate (PODIC C126) and dilauroyl peroxide (LP) as peroxides. For blending two virgin and three recycled PPs like coffee caps, yoghurt cups and buckets with different melt flow rate (MFR) values were used. The influence of using blends was assessed by investigating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 84 publications
0
12
0
1
Order By: Relevance
“…Another possibility for modifying rPP could be compounding with virgin polymers. While there is research available for other applications [ 13 , 14 , 15 ], no preceding research could be found for creating and assessing thermoforming compounds with post-consumer recyclate content.…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility for modifying rPP could be compounding with virgin polymers. While there is research available for other applications [ 13 , 14 , 15 ], no preceding research could be found for creating and assessing thermoforming compounds with post-consumer recyclate content.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure a, the crossover points of each sample shifted to the lower left with a higher loading of GDAF. Because the vertical and horizontal shifts of the crossover point represent the molecular weight distribution and relaxation time of the samples, respectively, , the results suggest a broadened spectrum of different molecular species and longer relaxation time of PTGs with higher GDAF loadings due to the presence of more branches and chain entanglements in these cases.…”
Section: Resultsmentioning
confidence: 96%
“…More than half of the world’s plastic production is composed of polyolefins. Polypropylene (PP) is one of the most important polyolefins of industries and our everyday lives with a global market size of US$75 billion in 2020 and an annual growth rate of 5.2% during the 2021–2028 period because of its low price, nontoxicity, excellent chemical resistance, high tensile strength, stiffness, and low density. PP is composed of two simple elements: C and H, and it is mainly produced with Ziegler–Natta or metallocene catalyst technology to generate mostly linear chain architecture, which suggests limited structural diversity and functional groups. In particular, PP lacks melt strength and strain hardening properties due to its linear chain characteristic, which makes it difficult to use in foaming, extrusion coating, and blow molding processes. …”
Section: Introductionmentioning
confidence: 99%
“…The high cost of separation is no longer a hurdle given the homogeneity and significant amount of polypropylene PPE waste during the COVID19 pandemic. With adequate source separation, polypropylene PPE can be remelt and mixed with virgin material [ 13 ] at up to 50% to produce new products such as playground equipment, plastic gardening tools, and carpets.…”
Section: Short-term Responsementioning
confidence: 99%